NEKE METRIJSKE KARAKTERISTIKE TESTOVA ZA PROCJENU BRZINE LETA LOPTE TOKOM JEDNORUČNOG IZBAČAJA - Nikola Foretić; Ognjen Uljević; Ante Prižmić (University of Banja Luka, Faculty of physical education and sport, 2010)
The aim of the study was to determine metric characteristics of the 2 tests for evaluationhandball ball speed during over arm throw of handball ball. Research was conducted on a sampleof 50 students of the Faculty of kinesiology, average age of 20.4 years. Beside measurements ofbody height and body weight, speed of ball flight after over arm throw from sitting position (dis-tance 4 meters) was assessed with radar gun. The tests of over arm throw were performed with ablocked and a free hand which does not perform a throw. Results show satisfactory reliability,sensitivity and validity of all tests. The homogeneity of tests was not good considering that thepositive trend of results was observed. This is a consequence of respondent adaptation to thetechnique of over arm throw performance. Factor analysis extracted a latent dimension that maybe called a factor of the ball speed during overarm throw performance. Respondents achievedsignificantly better results in the test RS because of biomechanical freer movement. This alsoconfirmed the pragmatic validity of the tests. The tests are best for use in sports like handball,water polo, tennis, volleyball, baseball or throwing disciplines in athletics because of the similarityof overarm performance and technical elements of the chosen sport. The advantages of tests arefast performance, easy execution and good metric characteristics and the defects poor homoge-neity and necessity for a radar gun.